Cloud Computing Third International Conference, CloudComp 2012, Vienna, Austria, September 24-26, 2012, Revised Selected Papers - Yousif, Mazin; Schubert, Lutz.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post conference proceedings of the Third International Conference on Cloud Computing, CloudComp 2012, held in Vienna, Austria, in September 2012. The 14 revised full papers were carefully reviewed and selected from numerous submissions and cover various topics in the application of cloud computing technologies.
The Need to Comprehend Clouds: Why We Still Can$1 (Bt Use Clouds Properly -- Assessing the readiness to move into the cloud -- Design and Implementation of a Multi-objective Optimization Mechanism for Virtual Machine Placement in Cloud Computing Data Center -- Agent Based Application Tools for Cloud Provisioning and Management -- Performance Evaluation of Embedded Processor in MapReduce Cloud Computing Applications -- Power-Aware Autonomous Distributed Storage Systems for Internet Hosting Service Platforms -- Specifying cloud application requirements: an ontological approach -- Opinion Model Based Security Reputation Enabling Cloud Broker Architecture -- Biometric Identity Trust: Toward Secure Biometric -- Enrollment in Web Environments.s
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer Science; Software Engineering; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).